Successful Management of Congenital Dyserythropoietic Anemia Type I with Interferon Alpha in a Child - Yarali, N.; Fišgin, T.; Duru, F.; Atílla, P.; Müftüoǧlu, S.F.; Kaymaz, S.F. (Taylor & Francis Inc, 2005)
Congenital dyserythropoietic anemia type I (CDA I) is a rare inherited hematological disorder characterized by macrocytic anemia and ineffective erythropoiesis with pathognomonic morphological features that include internuclear chromatin bridges, spongy heterochromatin, and invagination of the cytoplasm into the nuclear area in erythroid precursors. Treatment of anemia with the usual hematinics is without effect and 15% of patients need chronic transfusions. Successful treatment of CDA I with interferon-α was noted. The authors report a patient with CDA I who had required transfusions every 2-3 months since the neonatal period and responded to recombinant interferon-α therapy with the findings of electron microscopic investigations.
Keywords: Congenital Dyserythropoietic Anemia Type I; Interferon-Α